JUSTIFICATION OF RESEARCH ON SYSTEM OPTIMIZATION OF SURGICAL DENTAL CARE TO PATIENTS WITH HIV INFECTION. ANALYTICAL REVIEW OF LITERATURE - E. A. Bazikyan; A. S. Belyakova; I. V. Pchelin (Журнал инфектологии, 2018)
The article presents an analysis of the Russian and foreign specialized literature on the problem of dental rehabilitation of patients with HIV infection. It has been revealed that the structure and prevalence of dental surgical pathology in HIV infection has not been studied to date, the indices of the need for treatment of diseases of the dental profile have not been determined. Unsatisfactory access to qualified dental care has been identified, including due to discrimination and stigmatization by health professionals regarding both the disease itself and patients with HIV infection. The urgency of improving the system of rendering surgical dental care to HIV-infected with the aim of ensuring the maximum achievable level of health is substantiated. The data of the presented analytical review represent an important theoretical basis for the development of new tactical approaches to the implementation of the strategic direction of dental implant treatment of people living with HIV to expand access to this medical service.